Distance education: community college students' perspectives and attitudes toward online courses - Aljarrah, Abdelmuhdi, author; Gloeckner, Gene W., advisor; Johnson, Russell, committee member; Jansen, Duane, committee member; Davies, Timothy Gray, committee member; Kosiol, Chris, committee member (Colorado State University. Libraries, 2000)
The purpose of this study was to establish evaluative data about online courses from community college online students. These data contributed to a growing baseline of information and knowledge that may serve to develop and improve of online courses. The first section of the research established a demographic profile of community college students taking online courses. The second and third sections explored some of the online students' perceptions and attitudes toward online courses The analyses of the data revealed the following demographic findings (N=138). All online courses in this study were above the academic 100-level and were considered transferable courses. More females (69 percent) than male students were represented in the sample. The majority of the students were white (85 percent). Most of the students' ages were greater than twenty-five years old (77 percent). The majority of the participants were working full-time (83 percent). About 51 percent of the participants reported that they had children (aged 0-5 years old). Responses showed that all of the participants in this study used e-mail to communicate with their instructors, and 47 percent used bulletin boards. Thirty-two percent of the students used e-mail to communicate with other classmates. The data revealed positive perceptions by students about the value of online courses. The data also revealed that: there were differences among community colleges about how students felt about online courses; there were statistically significant differences in mean scores between the overall satisfaction of males and females in their perceptions toward online courses (females reported greater "Overall" scores than did males); there were no differences in mean scores between those of white ethnicity and others in their perceptions toward online courses; and there were statistically significant differences in mean scores between the older and younger groups in their perceptions toward online courses (older student reported significantly higher scores). The numbers of online courses taken were not associated with differences in students' perceptions toward online courses. Employment was not associated with differences in students' attitudes and perceptions toward online courses. Finally, the subject's family status (having children at home aged 0-5 years) did affect the overall perceptions and attitudes of subjects toward online courses.
Keywords: vocational education; community colleges; higher education; educational technology